SOSIALISASI PENERAPAN LESSON STUDY ACTIVITY (LSA) SEBAGAI UPAYA DALAM MENINGKATKAN KEMAMPUAN GRAMMAR SISWA PADA GURU BAHASA INGGRIS DI SMK PGRI 2 KOTA CIMAHI - Ningtyas Orilina Argawati; Ratih Inayah (Abdimas Siliwangi, 2020)
The socialization of the application of Learning in schools that aims to improve the quality and teaching and learning activities in schools in order to increase the ability in the material about English grammar that is expected to foster creativity, increase intelligence, and increase the effectiveness for each individual. In applying these lessons, the role of the servant is to provide socialization including jigsaw techniques that are applied as attractive cooperative learning techniques to be applied in the classroom. Implementation of Lesson Study This activity is carried out in 3 cycles, where each cycle consists of planning (planning), implementation (doing), and reflection (see). The results of devotion show a significant development in student learning where the motivation that appears can be overcome properly. In the end, after successfully the need for Lesson Study is implemented, teachers in schools can practice Lesson Study in the process of learning English at school.